(Dis)trust in doctors and public and private healthcare institutions in the Western Balkans - Driton Maljichi; Blerim Limani; Troy E. Spier; Violeta Angjelkoska; Sanja Stojković Zlatanović; Drita Maljichi; Iliriana Alloqi Tahirbegolli; Bernard Tahirbegolli; Ahmed Kulanić; Irida Agolli Nasufi; Milica Kovač‐Orlandić (Wiley, 2022)
Abstract Introduction Considering the geopolitical changes in the six Western Balkan countries-Albania, Bosnia and Herzegovina, Kosovo, Montenegro, North Macedonia and Serbia-over the last three decades, particularly as it concerns the progress and changes in the healthcare systems, we argue that there is a need for a detailed analysis of people's trust in those healthcare systems and healthcare providers. Methods In this cross‐sectional, intercountry study, we examine the trust trends of Western Balkans citizens in medical doctors and public and private healthcare institutions from 25 July 2021 to 30 October 2021, with 3789 participants using a self‐reported questionnaire, and Google Forms. Snowball sampling is used to collect data from six Western Balkans countries: Albania, Bosnia and Herzegovina, Kosovo, Montenegro, North Macedonia and Serbia. Findings The primary findings of our study show that citizens in the Western Balkans have a low level of trust in their healthcare system (X̄ = 4.3/10). Medical doctors working in private healthcare institutions, on the other hand, are afforded a higher level of trust (X̄ = 6.6/10) than those working in public healthcare institutions (X̄ = 5.7/10). In the event that they or their family members need to visit a health institution, half of the study participants would choose private healthcare institutions over public ones. We found a statistically significant difference between countries on the mean points from the questions concerning one's trust in the healthcare system, private healthcare institutions and medical doctors working in public and private sectors (p < .05). Conclusion Despite its limitations, this study is the first cross‐sectional research on the 'trust interface' among western Balkan citizens, revealing that they have low trust in their healthcare systems. Public Contribution The information in this manuscript was gathered on the level of 3789 citizens from six Western Balkan countries. Before we began collecting data, we conducted a piloting procedure with 40 citizens who were clients of health institutions to validate the data collection questionnaire.